Pemasaran Digital Street Food Pecel Lele di Kawasan Perguruan Tinggi Jalan Raya Jatinangor Kabupaten Sumedang - Sakira, Kekey; Gumilar, Iwang; Alfina, Alfina; Herman, Roffi Grandiosa; Maulina, Ine (Universitas Mataram, 2025)
Online applications are something that currently cannot be separated from people's lives, especially urban communities. The opportunity to utilize online applications is also applied in food sales based on the use of online applications, especially for sellers in the category of Micro, Small and Medium Enterprises (MSMEs). Activities that utilize online applications are called Electronic Commerce (E-Commerce) where physical contact is not required between sellers and buyers. Online applications are one of the things that can support economic progress, but the use of online applications for sales is still limited depending on the area, areas with poor internet conditions usually rarely use online applications for sales. The purpose of this study was to determine how much the marketing of fishery products (Pecel lele) using online applications along the Jatinangor highway which is an area with a high percentage of students and high potential for internet use. The conclusion of this study shows that most of the pecel lele stalls along Jalan Raya Jatinangor have used online applications for sales and fifty percent of pecel lele stalls stated that turnover from using online applications tends to be higher than conventional sales. The conclusion of this study is that in 12 catfish pecel stalls located along the Jatinangor highway, 75% of all stalls have online applications for sales and 25% do not have online applications for sales. In the turnover obtained, 6 out of 12 catfish pecel stalls get higher turnover profits, 3 out of 12 catfish pecel stalls have decreasing turnover profits, the remaining 3 stalls that do not use online applications do not experience changes in turnover profits, namely sales do not increase or decrease.